Experience in African swine fever control in the Russian Federation and its value for the other countries - K. N. Gruzdev; A. K. Karaulov; A. S. Igolkin (Ветеринария сегодня)
Basic characteristics of African swine fever, being one of the most significant transboundary infections with a devastating potential for pig production, are presented in the paper. It occurred in Georgia for the first time in 2007 and spread among domestic pigs and wild boar in the European part of the Russian Federation. After that, ASF virus was detected in Belarus, Ukraine and since 2014, the disease has been reported in the European countries. Having spread in Europe, African swine fever became an epizooty, caused by ASFV genotype II and exhibiting a deteriorating trend. Modern ASF infected areas in the Russian Federation, Europe, China and Asia are described. Currently the disease is the most serious epidemiological problem due to huge losses (high mortality among susceptible animals); ability to occur and spread in the most unexpected parts of the world and absence of specific prevention tools and means. Russia has developed a high level of expertise in the disease prevention, control and eradication. A scientifically justified set of measures to prevent and eradicate ASF, which has proved its effectiveness in the disease control, was developed and introduced. The core of this set is formed by biosafety assurance along the whole production chain at the establishments of any type of ownership involved into breeding, keeping, slaughter, processing, storage, movement and marketing of live pigs and pig products; by wild boar population control and improvement of waste management approaches. Other ASF infected countries can benefit from the Russian Federation’s experience in ASF control by adapting it to the concrete region with due regard to local social and economic conditions.